Therapeutic effects of garden : preference of ill children towards garden over ward in Malaysian Hospital Environment - Said, Ismail (Penerbit UTM Press, 2003)
Hospitalisation often erodes the feelings of toddlers and young children causing regressive behaviours and stress, which result in reduced cognitive performance, helplessness, restlessness, crying, anxiety, and elevated blood pressure. Having the ill children experience a garden setting at Batu Pahat Hospital and Segamat Hospital, they showed remarkable preferences and positive behaviours to the garden than the ward. The attributes of the garden that contribute to the positive responses include refreshing smell, fresh air, good-lighting, cheerful environment, pleasant sounds, scenic view, open space, freedom to play, at home feeling, and a variety of activities. These attributes are attained because the garden possesses three factors: (1) proper site planning with several play zones, (2) diversity of garden character, and (3) contact with microclimatic factors.